1974
DOI: 10.1104/pp.54.6.852
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Germination-promoting Substances Given in Conjunction with Red Light on the Phytochrome-mediated Germination of Dormant Lettuce Seeds (Lactuca sativa L.)

Abstract: Ethylene or thiourea can substitute for gibberellic acid but not for red light in breaking the secondary dormancy induced by extended dark storage of fully hydrated lettuce seeds (Lactuca sativa cv. Grand Rapids). After 10 days of storage, ethylene, thiourea, or gibberellic acid applied either separately or in any combination in conjunction with red light induced near maximal germination. When applied separately without red light, none of the substances promoted germination of seeds stored 10 days. Combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

1980
1980
1992
1992

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 7 publications
1
18
0
Order By: Relevance
“…5 (29). However, as KIN + ETH + GA4+7 is more active than GA4+7 in light or in darkness (Table III), the effect of KIN + ETH component might be separated from those of GA4+7 and/or Pfr.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…5 (29). However, as KIN + ETH + GA4+7 is more active than GA4+7 in light or in darkness (Table III), the effect of KIN + ETH component might be separated from those of GA4+7 and/or Pfr.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies have shown that secondary dormancy is imposed in seeds of lettuce and several weed species by prolonged dark imbibition in water (16,29,32,35), in an osmoticum (16,15), at supraoptimal temperatures (12,13), in anaerobic conditions (8) or in the soil (8,31,36). In several of these studies exposure to light of various durations or intensities broke the secondary dormancy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations